YOUTH ACTIVISM: THE ROLE OF YOUNG PEOPLE IN SOCIAL CHANGE - Santoshkumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Youth activism has become an increasingly influential force in driving social change across the globe, with young people actively challenging social, political, and environmental injustices. This movement is fueled by the passion, energy, and idealism of young individuals who seek to address issues such as climate change, racial and gender inequality, economic disparity, and political corruption. In the digital age, youth activism has expanded beyond traditional forms of protest, leveraging social media and digital platforms to amplify voices, mobilize communities, and hold governments and corporations accountable. This paper examines the significant role that young people play in social change movements, focusing on how they use collective action, advocacy, and innovative strategies to confront societal challenges. By exploring various examples of youth-led movements, such as global climate strikes, racial justice campaigns, and feminist movements, the paper highlights the diverse ways in which youth are shaping public discourse and influencing policy decisions. Young activists often challenge entrenched power structures, push for progressive reforms, and demand action on pressing global issues. The paper also discusses the empowerment of youth through education, leadership development, and grassroots organizing, which equip them to lead movements that generate lasting social and political impact. It underscores how youth activism serves not only as a tool for addressing contemporary issues but also as a catalyst for fostering solidarity across generations and borders. By examining the intersection of youth engagement, activism, and social change, the paper demonstrates the essential role of young people in creating a more just, inclusive, and sustainable world. Ultimately, youth activism is not only about advocating for present-day issues but ensuring a better future for all.